Kompleksitas Pelaksanaan Penertiban Penjualan Minuman Beralkohol Dalam Operasi Yustisi - Yudistira Bayu Aji; Sri Widayanti (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study is titled "The Complexity of Alcohol Beverage Sales Regulation in Yustisi Operations (Case Study of the Special Region of Yogyakarta)". In the Special Region of Yogyakarta, there are individuals who sell alcoholic beverages without a permit, marketing their products in certain areas and even online with instant delivery systems. According to Regional Regulation Number 12 of 2015, the Satuan Polisi Pamong Praja DIY has the authority to control and supervise alcoholic beverages. This study aims to understand the complexity of regulating alcoholic beverage sales in Yustisi operations within the Special Region of Yogyakarta. This research uses a qualitative method with a descriptive approach. The research location is at the Satuan Polisi Pamong Praja DIY, using data collection techniques through observation, interviews, and documentation. The number of informants in this study is 7 people. The results of this study show that in the Special Region of Yogyakarta, there are individuals who sell alcoholic beverages without a permit and market their products in certain areas, even online with instant delivery systems. Yustisi Operations are legal actions undertaken by the government, where the Satuan Polisi Pamong Praja DIY is authorized to take actions to maintain public order. The process of regulating the sale of alcoholic beverages through Yustisi Operations is known to have its own complexity. This complexity arises due to the presence of elements in the theory of complexity, namely interaction, dynamics, and mechanisms. This study concludes that the complexity in the implementation of alcoholic beverage sales regulation in the Special Region of Yogyakarta is influenced by various interacting and dynamic factors, as well as mechanisms that do not always operate as expected. These findings are expected to provide insights and contribute to the development of more effective strategies for regulating the sale of alcoholic beverages in the future.